Notch system is differentially expressed and activated in pituitary adenomas of distinct histotype, tumor cell lines and normal pituitaries - Perrone, Sofía (2017)
Pituitary adenomas are among the most frequent intracranial neoplasms andtreatment depends on tumor subtype and clinical features. Unfortunately, nonresponder cases occur, then new molecular targets are needed.Notch system component expression and activation data are scarce in pituitarytumorigenesis, we therefore aimed to characterize Notch system in pituitary tumors of different histotype. In human pituitary adenomas we showed NOTCH1-4 receptors, JAGGED1 ligand and HES1 target gene expression with positive correlations between NOTCH1,2,4 and HES1, and NOTCH3 and JAGGED1 denoting Notch system activation in a subset of tumors. Importantly, NOTCH3 positive cells were higher in corticotropinomas and somatotropinomas compared to non functioning adenomas. In accordance, Notch activation was evidenced in AtT20 tumor corticotropes, with higher levels of NOTCH1-3 active domains, Jagged1 and Hes1 compared to normal pituitary.In the prolactinoma cell lines GH3 and MMQ, in vivo GH3 tumors and normalglands, Notch system activation was lower than in corticotropes. In MMQ cells only the NOTCH2 active domain was increased, whereas NOTCH1 active domain was higher in GH3 tumors. High levels of Jagged1 and Dll1 were found solely in GH3 cells, and Hes1, Hey1 and Hey2 were expressed in a model dependent pattern.Prolactinomas harbored by lacDrd2KO mice expressed high levels of NOTCH1active domain and reduced Hes1.We show a differential expression of Notch system components in tumoral andnormal pituitaries and specific Notch system involvement depending on adenomahistotype, with higher activation in corticotropinomas. These data suggest thattargeting Notch pathway may benefit non responder pituitary adenomas.